Frequency Regulation of Micro-grid Connected Hybrid Power System with SMES - Singh S.; Verma R.K.; Shakya A.K.; Pratap Singh S. (My University, 2025)
This paper presents the frequency regulation analysis of a micro-grid connected hybrid power system based on solar Photovoltaic (PV), Wind and Diesel-Engine Generator (DEG) with Superconducting Magnetic Energy Storage system (SMES) unit. Abrupt change in load demand and power fluctuations from PV and wind power source causes frequency variability in the system. In order to mitigate this issue, the hybrid power system incorporates along with the energy storage devices. A case study of the impact of SMES operations on the performance of frequency stability of hybrid system has been carried out. Simulation of a Hybrid Power System (HPS) model has been carried out in two different scenarios with the two phases. First is the steady state investigation of HPS using PI controller with step load change response. Second is the dynamic performance study throughout a typical day with arbitrary variation in load demands. Controller parameters are tuned with Genetic Algorithm based optimization approach. The limits on the inductor (coil) current due to the possibilities of discontinuous conduction in the presence of large disturbances and limited storage capacity have also been incorporated. HPS has analyzed in the Matlab Simulink environment. Simulation results indicate that SMES system can contribute towards the frequency stability in both cases for variable power generations from renewable sources and irregular demand loads. © 2017, Springer Nature Singapore Pte Ltd.